O utilitarismo kantiano de R. M. Hare - Bernardes, Cleide (2009)
This dissertation analyses the main topics of Hare s ethical theory by the light of one of his main thesis, the one that says it is possible to consistently reconcile teleological and deontological aspects in a kind of kantian utilitarianism. To that, we analyzed structural concepts of Hare, and, giving special attention to meta-ethics analysis about normative concepts and some misunderstood interpretations of them, we highlight how Hare´s Kantian Utilitarianism is constructed in his original meta-ethics (universal-prescriptivism), its normative applications (as in his theory of the two levels of moral thinking), and in his critical relationship to kantian ethics. Chapter one addresses concepts and divisions in general normative ethics and it tries to show the main topics of Mill s classical utilitarianism and Kant s deontological ethics, generally seen as opposites each other by moral philosophy. We presented Mill s classical utilitarianism and its reformulation of Bentham s principle of utility, intending to demonstrate that, if well understood, it is not contrary to kantian ethics. Through Mill s assurance that there are teleological elements in Kant s deontological ethics, we presented in this chapter a brief approach of Kantian ethics in the main topics of Groundwork of the Metaphysic of Morals, since these two ethical views are fundamental for Hare s ethical proposal. The possibility of conciliation between utilitarianism and Kantian ethics was the theme developed on chapter two, in which we analyzed the deontological rational form of the moral statements and the related teleological preferencial-utilitarian content in Universal Prescriptivism. We also presented the normative structure of Hare s theory in three interconnected thesis, the universal prescriptivity of moral concepts (of ordinary language) [1], the equal consideration or impartiality as in the Golden Rule [2], and the need to find the action that maximizes the satisfaction of desires [3]. The way such theory is applied in a coherent form to the real world s dilemma, i.e., having two application levels, an intuitive, with general rules for the daily life, and a critical, with specific situations analyses at theoretical reflection, ends the chapter. The chapter three discusses some critiques to Hare´s Kantian utilitarianism, specially his attempt to conciliate consequentialism and deontological norm of respect for persons. At the end of this dissertation, we have defended the legitimacy and consistence of Hare s ethical theory, and we finish showing how the theory fulfills Beauchamp and Childress (2002) principlist conditions for a good ethical theory.